Outcomes and impacts of CGIAR Research Initiatives in Kenya from 2022 to 2024 - Boukaka, Sedi Anne; Kimaiyo, Faith; Kramer, Berber; Ayalew, Hailemariam; Place, Frank (International Food Policy Research Institute, 2025)
Kenya hosted one of CGIAR’s largest portfolios of research and innovation from 2022 to 2024, when pooled funding for the CGIAR was distributed through CGIAR research initiatives. This paper synthesizes CGIAR’s contributions to Kenyan agriculture in that period by triangulating two evidence streams: 148 outcomes logged in the CGIAR Performance and Results Management System (PRMS) and 56 impact assessments published as peer-reviewed journal articles. The analysis shows that CGIAR’s work has catalyzed improvements in seed systems, facilitated refinements in agronomic techniques, and encouraged the adoption of climate-resilient, sustainable farming practices and technologies. These contributions have paved the way for increasing crop productivity, while also supporting key livestock innovations that enhance food safety and bolster the resilience of pastoral communities. Robust local partnerships underpinned several policy shifts and helped align many outputs with the Bottom-Up Economic Transformation Agenda (BETA). Yet, important gaps persist. Activities are mainly concentrated in easily reached areas rather than being spread across all agro-ecological zones, and outcomes are recorded in an isolated way, obscuring how separate successes add up to systemic change. Peer-reviewed impact evaluations focused on a different set of impact areas than outcomes reported in PRMS, rarely involve cross-center collaborations, and PRMS entries seldom document how evidence, policy uptake, and multidisciplinary collaboration link together. Looking ahead to the next CGIAR Science Programs phase, the paper urges broader engagement with under-served value chains, deeper cross-program synergies, and closer alignment with Kenya’s BETA and MTP IV priorities to foster inclusive, resilient agricultural growth.